Seprafilm superior to Gore-Tex in the prevention of peridural fibrosis - Topsakal, C; Akpolat, N; Erol, FS; Ozveren, MF; Akdemir, I; Kaplan, M; Kilic, N (Amer Assoc Neurological Surgeons, 2004)
Object. This is an investigation into the effects of two barrier membranes in the prevention of peridural fibrosis in an animal model. Methods. Seprafilm or Gore-Tex was applied to a laminectomy defect overlying the dura mater in rats separated into treatment groups. A third group of rats underwent laminectomy only and served as controls. Two months postoperatively a histological study was performed to compare the amount of scar tissue in each group. The gross dissection demonstrated that both membranes created a controlled dissection plane, facilitated access to the epidural space, and provided a reduction in the amount of tissue adhering to the dura mater. Statistically, Seprafilm was superior to Gore-Tex in preventing peridural fibrosis (p < 0.05). Conclusions. Seprafilm can prevent peridural fibrosis better than Gore-Tex and can be used in humans in spinal surgery.
Keywords: adhesion; peridural fibrosis; scar; Gore-Tex; seprafilm